Un nouveau bâtiment du cloître de Saint-Hilaire-le-Grand à Poitiers (xe-xive siècle) - Emmanuel Barbier; Anne Jégouzo (Archéologie Médiévale, 2016)
The rescue archaeology operation conducted in the cloister of Saint-Hilaire-le-Grand in Poitiers allowed to study a new building on the southern edge of the collegiate church. Covering an area of 170 m2 on two very well-preserved levels, it is a representative example of the architectural and topographical evolution of cloisters. Founded on a late antique base, this building went through five major construction phases until its reorganization in the 19th century. The first great constructions were carried around the 10th century when a monumental fence was built to keep a consecrated and a civil space separate. The location and the outstanding dimensions of this stonework suggest that a claustrum or a castrum might have existed. In the 11th century, a huge pantry was created against this boundary, which led to important changes in the traffic within the cloister and its organization. The whole structure underwent significant changes with the opening of new access points, the partition of the inner space and the installation of a floor still preserved today.